2015
DOI: 10.2105/ajph.2015.302591
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Hepatitis C Incidence Among a Population With Repeated Tests: British Columbia, Canada, 1993–2011

Abstract: Addictions treatment, harm reduction, prevention education, and novel initiatives to remove barriers in health infrastructure need to be intensified for those who inject drugs, particularly men and younger persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…HBV co-infection and mental health problems were significantly associated with increased odds of new infection but decreased odds of prevalent HCV infection, while ORs for illicit drug use compared to no drug use among new infections (AOR = 21) were four times than those for prevalent HCV infection (AOR = 5.0). ORs for prevalent HCV infection were highest for birth cohort 1945-64 and declined thereafter, while among new infections, ORs were highest for those born later, consistent with an earlier analysis demonstrating a higher HCV incidence rate in younger birth cohorts [ 25 ]. Demographic characteristics and risk factors for prevalent HCV were also consistent with recent data from the United States and Canada [ 8 , 20 ].…”
Section: Discussionsupporting
confidence: 83%
“…HBV co-infection and mental health problems were significantly associated with increased odds of new infection but decreased odds of prevalent HCV infection, while ORs for illicit drug use compared to no drug use among new infections (AOR = 21) were four times than those for prevalent HCV infection (AOR = 5.0). ORs for prevalent HCV infection were highest for birth cohort 1945-64 and declined thereafter, while among new infections, ORs were highest for those born later, consistent with an earlier analysis demonstrating a higher HCV incidence rate in younger birth cohorts [ 25 ]. Demographic characteristics and risk factors for prevalent HCV were also consistent with recent data from the United States and Canada [ 8 , 20 ].…”
Section: Discussionsupporting
confidence: 83%
“…In addition, as people age, their drug use pattern also changes. In our other analyses, we have seen that incidence of HCV was much lower in older birth cohorts compared to those born after 1975 [ 32 ]. Another phenomenon could be aging of the population who inject with fewer younger people initiating injecting.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study may overestimate the number of undiagnosed people in BC, and the observed decline in prevalence may be larger than we estimate here. Declining HCV prevalence is not only driven by increased treatment and cure achieved by DAAs, as new/incident HCV cases have fallen in BC over the last decade, as have people who test positive the first time that they are tested, and mortality among people affected by HCV is significantly higher, compared to those who have tested negative for HCV. There may also be some bias in the classification of history of mental illness and substance use.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) infection remains a leading global cause of morbidity and mortality, despite declining incidence of HCV infection in many settings. Morbidity and mortality related to chronic HCV infection continues to increase, driven by large populations of people living with HCV who acquired the infection decades ago.…”
Section: Introductionmentioning
confidence: 99%